The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1097/01.jpn.0000311876.38452.fd
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Major Newborn Birth Injuries

Abstract: A classification system of various forms of major newborn birth injuries is clearly lacking in the literature. Currently, no scales exist for distinguishing degrees, extent, or distinctions of major birth injuries. The purpose of this study was to use published and online literature to explore the timing, prediction, and outcomes of major newborn birth injuries. Potential antecedents and causes were used in depicting what were reported to be major birth injuries. The outcome of this literature search was the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…Through a population‐based national estimate it was determined that the rate of birth trauma in the US is higher than a majority of studies have previously reported. Health professionals may have the ability to decrease the number and rate of infants diagnosed with birth trauma by recognising perinatal risk factors for birth trauma and using technological advancements (such as ultrasonography and fetal monitoring) before attempting a vaginal delivery 19 . In addition, further birth trauma research, including more in‐depth classification (such as an expansion of the work done by Pressler 19 ) and follow‐up of infants who are diagnosed with birth trauma, will better quantify the morbidity and mortality of birth trauma by type and among infants and women with various birth trauma risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through a population‐based national estimate it was determined that the rate of birth trauma in the US is higher than a majority of studies have previously reported. Health professionals may have the ability to decrease the number and rate of infants diagnosed with birth trauma by recognising perinatal risk factors for birth trauma and using technological advancements (such as ultrasonography and fetal monitoring) before attempting a vaginal delivery 19 . In addition, further birth trauma research, including more in‐depth classification (such as an expansion of the work done by Pressler 19 ) and follow‐up of infants who are diagnosed with birth trauma, will better quantify the morbidity and mortality of birth trauma by type and among infants and women with various birth trauma risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Health professionals may have the ability to decrease the number and rate of infants diagnosed with birth trauma by recognising perinatal risk factors for birth trauma and using technological advancements (such as ultrasonography and fetal monitoring) before attempting a vaginal delivery 19 . In addition, further birth trauma research, including more in‐depth classification (such as an expansion of the work done by Pressler 19 ) and follow‐up of infants who are diagnosed with birth trauma, will better quantify the morbidity and mortality of birth trauma by type and among infants and women with various birth trauma risk factors. Prevention of birth trauma will also reduce the number of stresses that it places on the health care system because neonates with birth trauma were shown in this study to have higher costs, greater lengths of stay, and have more medical procedures than neonates not diagnosed with birth trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Birth-related injuries are not uncommon, but they account for fewer than 2% of neonatal deaths [4]. The rates of infant mortality due to birth trauma fell significantly during the last two decades.…”
Section: Discussionmentioning
confidence: 99%
“…In the immediate postnatal time period, a wide spectrum of extracranial, cranial (skull), and intracranial lesions may be encountered . Depending on the severity and type of the injury, location of the lesion, exerted mass effect on adjacent brain structures, development of primary (eg, anemia and hypovolemic shock in subgaleal hematomas), and/or secondary (eg, hyperbilirubinemia in subgaleal hematomas and secondary ischemic lesions in skull fractures with midline shift) complications and presence of complicating factors outside of the central nervous system (eg, systemic hypoxia, hypoperfusion, or sepsis), various degrees of reversible or irreversible brain injury may result.…”
Section: Parturitional Skull and Brain Injuriesmentioning
confidence: 99%
“…Intracranial injuries occur in 5–6/10,000 live births in the United States. Risk factors include forceps delivery (x6), vacuum extraction, prolonged delivery, and macrosomia . A variety of lesions may be encountered, which include all well‐known posttraumatic lesions like epidural hematoma (EDH), SDH, subarachnoid hemorrhage (SAH), IVH, and parenchymal contusion or laceration.…”
Section: Parturitional Skull and Brain Injuriesmentioning
confidence: 99%